Tradisi Pembacaan Q.S. Al-Lahab Sebagai Penangkal Hujan di Taman Pendidikan Al-Quran Baitul Mahfudh Madumulyorejo Dukun Gresik - Fithrotin; Habibah, Nur (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2024)
The practice of reciting Surah Al-Lahab as a rain deterrent at the Taman Pendidikan Al-Qur'an (TPQ) Baitul Mahfudh, Madumulyorejo, Dukun, Gresik, is a religious tradition that blends Quranic teachings with local wisdom to address environmental challenges, particularly extreme weather. This study aims to uncover the religious meanings and beliefs of the community regarding this tradition, as well as to understand how these values influence their religious practices. A qualitative approach was employed, utilizing interviews and participatory observation to explore the community's understanding of the Surah Al-Lahab recitation ritual. The results show that this tradition is perceived as a form of prayer to avoid rain, which could disrupt the community's activities. The ritual also reflects the connection between religious and social dimensions within the local community. In conclusion, the recitation of Surah Al-Lahab serves not only as a religious practice but also as a means to strengthen social solidarity and address environmental challenges within the community.